2015
DOI: 10.1039/c5cc02685g
|View full text |Cite
|
Sign up to set email alerts
|

Thioamides in the collagen triple helix

Abstract: To probe noncovalent interactions within the collagen triple helix, backbone amides were replaced with a thioamide isostere. This subtle substitution is the first in the collagen backbone that does not compromise thermostability. A triple helix with a thioamide as a hydrogen bond donor was found to be more stable than triple helices assembled from isomeric thiopeptides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
69
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 58 publications
1
69
0
Order By: Relevance
“…The PP S G modification shows a stabilization of the triple helix with a significant increase in T m and 0.4 kcal mol –1 increase in Δ G U , while PPG S shows a moderate destabilization, in agreement with previous studies. 24 Hysteresis studies showed that the free energy differences are in good agreement with the melting temperature profiles (Fig. S32–S36†).…”
Section: Resultssupporting
confidence: 54%
“…The PP S G modification shows a stabilization of the triple helix with a significant increase in T m and 0.4 kcal mol –1 increase in Δ G U , while PPG S shows a moderate destabilization, in agreement with previous studies. 24 Hysteresis studies showed that the free energy differences are in good agreement with the melting temperature profiles (Fig. S32–S36†).…”
Section: Resultssupporting
confidence: 54%
“…The intramolecular O…CO distance should be less than 3.2 Å and the corresponding bond angle 100°–120°. More recently, Raines and coworkers extended this investigation to endothioxopeptides (through the detailed NMR determination of their trans / cis ratios) and others to endothioxopeptoids. In the former compounds, theoretical analyses demonstrated that the energy of the n → π * interaction is higher when the donor atom is sulfur (as compared to oxygen).…”
Section: Resultsmentioning
confidence: 99%
“…Thioamides mimic the shape and structure of peptide bonds but present different electronic and hydrogen-bonding properties-making thioamides important biophysical probes of peptide structure and function. 1,2 For example, thioamides have been employed to interrogate hydrogen-bonding in α-helices and β-turn structures, [3][4][5] as well as n→π* interactions between peptides bonds across amino acids (i → i + 1). [6][7][8] Further, thioamides have been applied in photochemical isomerization schemes, 9,10 and can serve as quenchers of fluorescent probes to study peptide folding.…”
Section: Introductionmentioning
confidence: 99%